The agroecological transition of agricultural systems in the Global South - Côte, François-Xavier; Poirier-Magona, Emmanuelle; Perret, Sylvain; Roudier, Philippe; Rapidel, Bruno; Thirion, Marie-Cécile (éditions Quae, 2019)
"Food security, jobs, ecological transition of agricultural production models and consumption patterns... Agroecology could be one of the solutions to meet the future challenges of humanity. Part of the United Nation's 17 Sustainable Development Goals, it requires a lasting commitment from all of us. To meet the food and economic needs of growing rural and urban communities, fulfil increasingly demanding consumer requirements, conserve natural resources and adapt to climate change, we have to find new ways of agricultural production. Over the last decade, CIRAD and AFD have conducted experiments in agroecological transitions with farmers, researchers, development agents and policymakers in many countries of the Global South. In this book, they reflect on the future of agroecology as a way for agriculture in the developing world to adapt to global changes and they examine the conditions necessary for a successful agroecological transition."